Postembryonic development and biology of Psammotettix alienus (Dahlbom) (Homoptera Cicadellidae) under laboratory conditions (Bollettino di zoologia agraria e bachicoltura, 2024)
Biological aspects on Psammotettix alienus (Dahlbom) were studied under laboratory conditions (27° C, 80% RH and 14L:10D of artificial light photoperiod). Egg and nymph stages were described and illustrated, pointing out those characters (presence or absence and length of wingpads, chaetotaxy of the abdomen and coloration pattern) useful to distinguish each instar. Duration of different developmental stages, life cycle, longevity, fertility, fecundity, survival, life expectance, net reproductive rate, generation time, intrinsic rate of increase and sex ratio were estimated. P. alienus completes its life cycle in approximately 43 days and the adults show a longevity of 16.2 days. Females lay a mean of 36.7 eggs with a range from 3 to 100 and a viability of 62.6%. The survivorship curve shows two periods of heavy mortality: the first one occurs before the ecdysis from first to second instar and the second one occurs from the first 4 to 8 days as imagoes. The net reproductive rate "Ro" was 11.42; the generation time "T" was 23 days and the intrinsic rate of increase "r" was ≅ 0.106. The natural enemies observed in field near Viterbo (ltaly) belong to the Dryinidae (Gonatopus clavipes (Thunberg) and G. lunatus Klug) and Pipunculidae (Eudorylas imperfectus (Becker) and Tomosvaryella sp.) families.
Keywords: Psammotettix alienus; postembryonic development; life cycle; populational parameters; natural enemies